Active learning for improving a soft subspace clustering algorithm. (November 2015) - Boulemnadjel, Amel; Hachouf, Fella; Hebboul, Amel; Djemal, Khalifa
Abstract: In this paper a new soft subspace clustering algorithm is proposed. It is an iterative algorithm based on the minimization of a new objective function. The classification approach is developed by acting at three essential points. The first one is related to an initialization step; we suggest to use a multi-class support vector machine (SVM) for improving the initial classification parameters. The second point is based on the new objective function. It is formed by a separation term and compactness ones. The density of clusters is introduced in the last term to yield different cluster shapes. The third and the most important point consists in an active learning with SVM incorporated in the classification process. It allows a good estimation of the centers and the membership degrees and a speed convergence of the proposed algorithm. The developed approach has been tested to classify different synthetic datasets and real images databases. Several indices of performance have been used to demonstrate the superiority of the proposed method. Experimental results have corroborated the effectiveness of the proposed method in terms of good quality and optimized runtime. Abstract : Highlights: A new objective function for subspace clustering is proposed. Clustering results are stabilized by an initial step based on the SVM algorithm. Incorporating SVM in the active learning has improved the results.